Cerebellar Symptoms in Crigler-Najjar Type I Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Three children with Crigler-Najjar (CN) type I disease who had cerebellar symptoms as the initial manifestation of kernicterus are reported from the Hopital Antoine Beclere, Clamart Cedex, France.